Enhanced TLR7-dependent production of type I interferon by pDCs underlies pandemic chilblains - Saidoune, Fanny; Lee, Danyel; Di Domizio, Jeremy; Le Floc’h, Corentin; Jenelten, Raphael; Le Pen, Jérémie; Bondet, Vincent; Joncic, Ana; Morren, Marie-Anne; Béziat, Vivien; Zhang, Shen-Ying; Jouanguy, Emmanuelle; et al. (The Journal of experimental medicine, 2025)
Outbreaks of chilblains were reported during the COVID-19 pandemic. Given the essential role of type I interferon (I-IFN) in protective immunity against SARS-CoV-2 and the association of chilblains with inherited type I interferonopathies, we hypothesized that excessive I-IFN responses to SARS-CoV-2 might underlie the occurrence of chilblains in this context. We identified a transient I-IFN signature in chilblain lesions, accompanied by an acral infiltration of activated plasmacytoid dendritic cells (pDCs). Patients with chilblains were otherwise asymptomatic or had mild disease without seroconversion. Their leukocytes produced abnormally high levels of I-IFN upon TLR7 stimulation with agonists or ssRNA viruses—particularly SARS-CoV-2—but not with DNA agonists of TLR9 or the dsDNA virus HSV-1. Moreover, the patients’ pDCs displayed cell-intrinsic hyperresponsiveness to TLR7 stimulation regardless of TLR7 levels. Inherited TLR7 or I-IFN deficiency confers a predisposition to life-threatening COVID-19. Conversely, our findings suggest that enhanced TLR7 activity in predisposed individuals could confer innate, pDC-mediated, sterilizing immunity to SARS-CoV-2 infection, with I-IFN–driven chilblains as a trade-off.